Distribution and Variation of Serotypes and Pneumococcal Surface Protein A Clades of Streptococcus pneumoniae Strains Isolated From Adult Patients With Invasive Pneumococcal Disease in Japan - Chang, Bin; Kinjo, Yuki; Morita, Masatomo; Tamura, Kosuke; Watanabe, Hiroshi; Tanabe, Yoshinari; Kuronuma, Koji; Fujita, Jiro; Oshima, Kengo; Maruyama, Takaya; Abe, Shuichi; Kasahara, Kei; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Pneumococcal surface protein A (PspA) is a surface protein of Streptococcus pneumoniae that may be a candidate antigen for new pneumococcal vaccines. This study investigates the distribution of PspA clades of the causative strains of adult invasive pneumococcal disease (IPD) in Japan. Of the 1,939 strains isolated from cases of adult IPD during 2014–2019, the PspA clades of 1,932 (99.6%) strains were determined, and no pspA was detected in the remaining 7 strains (0.4%). PspA clades 1–6 were detected in 786 (40.5%), 291 (15.0%), 443 (22.8%), 369 (19.0%), 33 (1.7%), and 6 (0.3%) strains, respectively. New PspA clades (0.2%) were identified in two non-typeable and two serotype 35B pneumococci. The proportions of clade 1 and clade 2 showed significantly decreased and increased trends, respectively. Furthermore, the PspA clade of pneumococcal strains was partially serotype- and sequence type-dependent. The majority of strains belonging to serotypes contained in both the 13-valent pneumococcal conjugate vaccine (PCV13) and the 23-valent pneumococcal polysaccharide vaccine (PPSV23) belonged to PspA clades 1 or 3. In contrast, the distribution of clades in non-vaccine serotypes was wider than that of vaccine serotype pneumococci. Our findings demonstrate that almost all pneumococcal strains from adult IPD express PspA clades 1–4, especially for non-vaccine serotypes. These results may be useful for the development of a new pneumococcal vaccine with PspA.